2019
DOI: 10.3389/fmolb.2019.00106
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Contributes to Restimulation-Induced Cell Death of Human CD4 T Cells

Abstract: Restimulation-induced cell death (RICD) is an apoptotic pathway triggered in activated effector T cells after T cell receptor (TCR) re-engagement. RICD operates at the peak of the immune response to ensure T cell expansion remains in check to maintain immune homeostasis. Understanding the biochemical regulation of RICD sensitivity may provide strategies for tuning the magnitude of an effector T cell response. Metabolic reprogramming in activated T cells is not only critical for T cell differentiation and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Nonetheless, the impact of FASN overexpression on mitochondria respiration had not been well studied until 2015. A positive association between FASN levels and oxidative phosphorylation rates has been reported across various cancer cell types and immune cells through the manipulation of FASN levels [ 77 , 90 ]. FASN overexpression is shown to generate excessive amounts of free FAs, which are then broken down into acetyl-CoA.…”
Section: Fasn Influences Organelle Activity In Tumor Cellsmentioning
confidence: 99%
“…Nonetheless, the impact of FASN overexpression on mitochondria respiration had not been well studied until 2015. A positive association between FASN levels and oxidative phosphorylation rates has been reported across various cancer cell types and immune cells through the manipulation of FASN levels [ 77 , 90 ]. FASN overexpression is shown to generate excessive amounts of free FAs, which are then broken down into acetyl-CoA.…”
Section: Fasn Influences Organelle Activity In Tumor Cellsmentioning
confidence: 99%
“…Recent study revealed blockade of FASN helped CD4 effector T cells effectively avoid restimulationinduced cell death (RICD) 43 . All the proof above displayed the close relationship between FASN and tumor immune response, while few studies concentrated on this aspect in BLCA for the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Further inhibition of the fatty acid-binding protein exclusively expressed in T cells, FABP5, enhances Treg suppression (Field et al, 2020). In a study of fatty acid metabolism and apoptosis sensitivity in primary human T cells, inhibition of FASN with C75 or siRNA knockdown significantly protected T cells from restimulationinduced cell death (RICD) by reducing the induction of FAS ligand (Voss et al, 2019). Therefore, FASN inhibition could be used to protect T cells from apoptosis in the TME caused by repeated TCR activation and boost T cell immunity in addition to its anti-tumor efficacy on cancer cells directly.…”
Section: Targeting Fatty Acid Metabolismmentioning
confidence: 99%